CSR Implementation in a Public-Sector Logistics Context - Azmi Muhammad Islam; Izza Kahla Syakira (Journal of Innovation, Business Management and Entrepreneurship, 2025)
This study explores the implementation of Corporate Social Responsibility (CSR) at PT Kereta Api Logistik (KAI Logistik), a state-owned logistics enterprise in Indonesia, through the lens of the Triple Bottom Line (TBL) framework. Using a qualitative observational method, the research documents how CSR initiatives are operationalized across social, economic, and environmental dimensions. The findings reveal that CSR activities ranging from employee training and literacy campaigns to sustainable logistics innovations and ecological restoration reflect a growing integration of sustainability principles into the firm’s organizational practices. Rather than being limited to compliance or image-building, CSR at KAI Logistik demonstrates alignment with national development goals and emerging public expectations around responsible state enterprise governance. This study contributes to the literature by providing contextualized insights into how TBL can be practically enacted in a public-sector logistics setting in an emerging economy. The paper also highlights the strategic potential of CSR as a vehicle for stakeholder engagement, institutional legitimacy, and sustainable development in state-owned enterprises.